(untitled) - Hagen, Chris (Gaithersburg, 1999)
In light of the expanding responsibilities of rehabilitation therapists from merely clinical to include the fiscal management of limited resources, Hagen, whose company is based in southern California, offers therapists and their managers a clinical decision-making model by which to transform.
Keywords: Phục hồi chức năng y tế,Medical rehabilitation